Network Analysis Reveals Tea Catechins as Multi-Target Inhibitors of Colon Adenocarcinoma - Anwar Rovik; Dyah Fitri Kusharyati (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Colon cancer is the second most common cause of cancer death worldwide. It drives the need for effective prevention and treatment strategies, including identifying new and inventive targets for treating colon cancer. This present study evaluated the potential of tea catechins against colon adenocarcinoma in silico. The study method includes a literature review, an analysis of protein targets and protein interactions, and network analysis. The prediction analysis showed that only epicatechin-3-gallate, epigallocatechin-3-gallate, and epigallocatechin potentially target colon cancer. These compounds target six common proteins in human cancer cells, such as AURKA, CA9, SERPINE1, MET, SQLE, and VEGFA. The analysis showed that the protein targets interact strongly with various proteins in human cancer cells. Therefore, tea catechin, especially epigallocatechin-3-gallate, can be explored as a colon cancer chemopreventive agent.